2017
DOI: 10.4103/0366-6999.201608
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neutrophil Extracellular Traps in Asthma and Chronic Obstructive Pulmonary Disease

Abstract: Objective:Asthma and chronic obstructive pulmonary disease (COPD) are representative chronic inflammatory airway diseases responsible for a considerable burden of disease. In this article, we reviewed the relationship between neutrophil extracellular traps (NETs) and chronic inflammatory airway diseases.Data Sources:Articles published up to January 1, 2017, were selected from the PubMed, Ovid Medline, Embase databases, with the keywords of “asthma” or “pulmonary disease, chronic obstructive”, “neutrophils” and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 70 publications
1
30
0
6
Order By: Relevance
“…In contrast to asthma, patients with chronic obstructive pulmonary disease (COPD) have progressive and generally irreversible airflow obstruction. Disease progression, GOLD (Global Initiative for Chronic Obstructive Lung Disease) status and exacerbations of COPD are connected to neutrophilia in lungs [3][4][5] . Asthma-COPD overlap syndrome (ACOS) is a consensus-based phenotype, not an individual disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to asthma, patients with chronic obstructive pulmonary disease (COPD) have progressive and generally irreversible airflow obstruction. Disease progression, GOLD (Global Initiative for Chronic Obstructive Lung Disease) status and exacerbations of COPD are connected to neutrophilia in lungs [3][4][5] . Asthma-COPD overlap syndrome (ACOS) is a consensus-based phenotype, not an individual disease.…”
mentioning
confidence: 99%
“…In the last decades, it has been discovered that neutrophils beside degranulation and phagocytosis can form neutrophil extracellular traps (NETs) to different triggers which process has been termed NETosis. In vivo, several biological molecules may elicit NETosis including interleukin-8 and tumor necrosis factor-α, both of which have a prominent role in asthma and COPD 3 . In vitro, the pharmacological agent phorbol-12-myristate-13-acetate (PMA) is a known strong inducer of NETosis that is routinely used in studies of NETs.…”
mentioning
confidence: 99%
“…[30][31][32] NETs also involve in the development of inflammation through inducing the release of cytokine by airway epithelial cells. Our experimental data suggested that NETs Increasing evidence has shown that NETs and their components cause damage of endothelial and epithelial cells, thus to impair pulmonary function and accelerate the progress of chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…129,130 However, an overabundance of NETs has been implicated in a number of lung diseases, such as CF, COPD, asthma, and acute respiratory distress syndrome. [151][152][153] Whether NETs could serve as a dsDNA source for cGAS-STING signaling activation needs further investigation. Oxidative stress and mitochondrial dysfunction also serve as a potential dsDNA origin in pulmonary disease.…”
Section: Directionsmentioning
confidence: 99%